The Description of Diphtheria Immunization History to Diphtheria Patients in Surabaya at 2017 - Ayu Fitriansyah (Universitas Airlangga, 2018)
Background: Diphteria can be prevented by immunization of DPT-HB-Hib (Diphteria, Hepatitis B, dan Haemophillus Influenze B) to infants and DPT-HB-Hib Booster, DT (Diphteria Tetanus) and Td (Tetanus Diphteria) afterwards. In 2017, diphteria case rate in Surabaya was high, 29 cases, due to the lack of 7 dosages of diphteria immunization. Purpose: This study aimed to depict the completion history of diphteria immunization based on the completness of immunization status which suits to age groups of diphteria patients in Surabaya in 2017. Methods: This study was quantitave descriptive with study cross research design. The objects of this study were diphteria patients in Surabaya in 2017 (29 individuals). Data was collected by quisionaire and immunization record from KIA/KMS books which belongs to Government effort to control Citizen Health Development. The variables of this study was diphteria patients characteristics (age and gender) and the history diphteria immunization. Data were analyzed using univariate analysis with frequency table.  Results: This study obtained that mostly the diphteria patients in Surabaya in 2017 suffered this disease in 18 until 84 months old (58.62%) and mostly happened to male (82.76%). All patients aged 18 months old received complete diphteria immunization (3.45%), but all patient aged more than ≥ 18 months old did not received complete diphteria immunization (96.55%). Mostly the patients did not receive re-immunization afterwards, i.e DPT-HB-Hib Booster, DT, and Td. Conclusion: The completion 7 dosages of diphteria immunization is important to diphteria cases, especially to diphteria re-immunization afterwards.